Didactic strategy and writing of written texts for 2nd grade students of IE 8183 Pitágoras. Puente Piedra. Lima - Caro Trujillo , Verónica Kohinta (2024)
The meaning and purpose of this scientific study is to know the relationship between the learning strategies and the written vocabulary of the second grade students of the educational institution N.8183 of the Puente Piedra district of Lima. Using quantitative methods, hypothetical-deductive method, transversal method, sequential level method, descriptive correlational design and using a sample of 60 students. Non-probabilistic information was collected using observation sheets and instruments, and the Likert scales were validated through expert ratings by three ad hoc juries and their reliability was determined using Crombach's alpha statistics. The data were analyzed using the Rho of the Spearman statistic, and the results showed that there is a high positive correlation of 0.801 between the text generation strategies and the composition of the written text of the 2nd year students of N educational institutions. 8183, is highly significant because the significance value is equal to 0.000 < 0.05, the null hypothesis is rejected and the alternative hypothesis is accepted. Therefore, it is concluded that text formation strategies depend on teaching strategies in the composition of written texts. Furthermore, text writing affects students' text generation strategies, since there is a very direct correlation between the two variables studied.